THE EVALUATİON OF İN-SERVİCE TRAİNİNG APPLİCATİONS OF THE MİNİSTRY OF NATİONAL EDUCATİON- KASTAMONU PROVİNCE CANDİCATE TEACHERS MODEL (Third Sector Social Economic Review, 2014)
The aim of this search is to investigate the evaluations, made by the candicate teachers, about preparatory and basic training seminars; in short in service training seminars, which are carried out regularly every year by the Ministery of National Education.This search is limited by the candidate teachers who were assigned in Kastamonu city- centre and districts in August, 2012. This search is an example of descriptive work in scanning model.This search includes the candidate teachers who were assigned to the high schools and primary schools in Kastamonu city-centre and districts. 226 candidate teachers were reached but just 179 of them filled out the questionnaire.In datum, it was identified that basic training and preparatory training is enough in terms of training place, accommodation and timing. The exams which were applied at the end of the training didn’t affect the training content, application, evaluation and working environment.
Keywords: Human resources management; In-service training; candidate teachers